Spectroscopic fluorescent tracking of a single molecule in a live cell with a dual-objective fluorescent reflection microscope. (17th October 2019) - Liu, Xiaolan; Yao, Longfang; Yang, Weidong; Fei, Yiyan; Mi, Lan; Ma, Jiong
Abstract: Single-molecule spectral imaging is a powerful technique for simultaneous study of biological samples labeled by multiple fluorophores. We have developed a robust prism-based single-molecule spectral tracking technique based on a dual-objective fluorescence–reflection system with tunable spectral dispersion (DOFR-SD). The system can capture the spatial position of a single molecule in real time, and rather than splitting photons into two channels its intrinsic spectral characteristics can also be captured without compromising the precision of the ( x, y ) position. Thus, the DOFR-SD technique is suitable for tracking the spectral variation of single particles in living cells and for multicolor coding.